The relationship between lexical fluency, temporal fluency, and language proficiency in Iranian EFL context - Yazdeli, Javad Rezazadeh; Mellati, Morteza; Mehdizadeh, Mostafa (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2016)
Lexical Fluency Units (LFUs) are strings of words that act like single items in language users’ mental lexicon. Recently, there has been a resurgence of interest in analyzing them in learners’ speech and classifying them into different types (Ushigusa 2008, Wood 2012). The literature in this particular field of study stated that the higher use of lexical fluency units might lead to the higher score on tests of oral English proficiency; therefore, the present study investigated the relationship between lexical fluency, temporal fluency (TF), and proficiency. To conduct the study, forty Iranian EFL teachers with TOEFL scores above 570 were chosen. To ensure that they have acquired competency in communication by which they can be employed as an instructor in the real context, they took an Oral English Proficiency Test (OEPT). Then, the sounds recorded from OEPT were analysed by PRRAT and Transcriber software and the transcripts of their responses were also analysed for detection of lexical fluency units (LFUs). Results indicated that teachers who incorporated more LFUs in their speech had higher TF ratio and consequently higher proficiency score. The interpretations and implementations are also discussed.